Antiulcer properties of Kelulut honey against ethanol-induced gastric ulcer - Saiful Yazan, Latifah; Zainal, Nurul Amira; Mohd Ali, Razana; Muhamad Zali, Muhamad Firdaus Shyfiq; Ong, Yong Sze; Tor, Yin Sim; Gopalsamy, Banulata; Voon, Fui Ling; Sapuan, Sarah; Esa, Nurulaidah; Haron, Aminah Suhaila; Zakarial Ansar, Fatin Hannani; et al. (Universiti Putra Malaysia Press, 2018)
Ulcers in the gastrointestinal tract refer to any appreciable depth of break in the mucosa lining that may involve submucosa. Common types of ulcer include peptic, gastric and duodenal ulcer, which may lead to chronic inflammation. Ulcers may be caused by excessive alcohol intake or prolonged use of non-steroidal anti-inflammatory drugs (NSAID), in addition to several other factors. Conventional medication such as Omeprazole (proton pump inhibitor) and Ranitidine (H2 blockers) for management of ulcers may cause severe side effects such as myelosupression and abnormal heart rhythm. This has driven researchers to explore the potential of natural products for management of ulcers with reduced side effects. Kelulut honey (KH) is a type of honey that is produced by stingless bees from the Trigona species. It is believed to have a lot of medicinal properties such as being antimicrobial, antioxidant and antidiabetic. Yet, no scientific study has been carried out on its antiulcer properties. This study was carried out to determine the antiulcer properties of KH. Eighteen male Sprague dawley rats (5 to 6 weeks old, weighing between 200 and 300 g) were divided into three groups (n=6). The groups were 1) normal control group (without ulcer, without KH), 2) positive control group (with ulcer, without KH) and 3) treatment group (with ulcer, treated with KH). The treatment, KH (1183 mg/kg), was given twice daily for 30 consecutive days by oral administration. On Day 31, the rats were induced with absolute ethanol (5 mL/kg) via oral administration after being fasted for 24 h and were sacrificed 15 min after the induction. The stomach was collected for macroscopic and histopathological evaluation. Pretreatment with KH significantly reduced (p<0.05) both the total area of ulcer and the ulcer index compared to the positive control group. The percentage of ulcer inhibition in the KH pre-treated group was 65.56% compared with the positive control group. The treatment, KH, exhibited antiulcer properties against ethanol-induced gastric ulcer.